Structure and Function of Roots 1995
DOI: 10.1007/978-94-017-3101-0_39
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of root growth by salinity stress: Toxicity or an adaptive biophysical response?

Abstract: This review considers mechanisms underlying the inhibition of root elongation growth by salinity stress. The first section considers effects of salinity on quasi steady state elongation growth, morphology and mature cell size, in maize (Zea mays L) primary roots. The following sections review evidence indicating that the inhibition of root elongation growth by salinity need not be a toxic consequence, e.g. of competitive displacement of essential Ca2+ from plasmamembrane binding sites in the expanding tip tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 28 publications
7
44
1
2
Order By: Relevance
“…It affects more than 10% of arable land and salinization is rapidly increasing on a global scale, declining average yield for most major crop plants by more than 50% (Bray et al, 2000). Salt stress occurs in areas where soils are naturally over salted and precipitation is low and/or where irrigation, hydraulic lifting of salty underground water, or invasion of sea water in coastal areas brings salt to the surface soil that inhabit plants (Neumann, 1995). Globally compatible solutes, have shown that increases in SS and/or other osmolytes provide optimism to increase plant tolerance to abiotic stresses such as drought, salinity and cold (Cusido et al, 1987;Rathinasabapathi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It affects more than 10% of arable land and salinization is rapidly increasing on a global scale, declining average yield for most major crop plants by more than 50% (Bray et al, 2000). Salt stress occurs in areas where soils are naturally over salted and precipitation is low and/or where irrigation, hydraulic lifting of salty underground water, or invasion of sea water in coastal areas brings salt to the surface soil that inhabit plants (Neumann, 1995). Globally compatible solutes, have shown that increases in SS and/or other osmolytes provide optimism to increase plant tolerance to abiotic stresses such as drought, salinity and cold (Cusido et al, 1987;Rathinasabapathi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous reviews of the effects of salinity on plant physiological processes and subsequent effects on yield (Greenway & Munns, 1980;Shannon et al, 1994;Neumann, 1995). In spite of this extensive literature there is still a controversy with regard to the mechanisms of salt tolerance in plants (Neumann, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity in the soil and irrigation water is a problem mainly in arid and semi-arid regions, and can severely limit crop yields or even make it impossible to grow certain plants (Shannon, 1998). However, despite extensive studies, there is still a good deal of controversy over plants' salt tolerance mechanisms (Neumann, 1995).…”
Section: Discussionmentioning
confidence: 99%